Accessibility, mobility, and realized travel behavior: Assessing transport disadvantage from a policy perspective. (February 2016) - Pyrialakou, V. Dimitra; Gkritza, Konstantina; Fricker, Jon D.
Abstract: Limited accessibility and mobility can result in decreased quality of life and well-being, as well as social exclusion. In the United States (U.S.), rural and small urban communities suffer from transport disadvantage due to a lack of transit and a low density of employment, education, recreation, and other opportunities. While the international literature has produced a number of methods and frameworks to assess transport disadvantage and its impacts, the U.S. has lagged behind in providing pertinent studies. The objective of this paper is to establish comprehensive measures that can support the identification, evaluation, and quantification of transport disadvantage in U.S. rural and small urban communities, considering both data availability and the unique characteristics of the U.S. The concept of transport disadvantage in this paper denotes the disadvantage of a specific population group or area that results from a difficulty accessing transportation and/or opportunities. To achieve this objective, this paper develops a spatial multi-perspective approach to account for the three essential elements of transport disadvantage: accessibility, mobility, and realized travel behavior. The developed approach provides an assessment of transport needs and need gaps that can be of benefit to small urban and rural communities and their planning practices, as well as to transport providers. The analysis in this paper suggests that—from a policy perspective—a combination of measures that account for all three essential elements of transport disadvantage should be considered, because the results of each measure complement those of the others. This paper illustrates the proposed approach using a case study of Indiana. The findings suggest that a great part of rural and small urban Indiana presents a low density of opportunities and that transport-disadvantaged residents of such areas might experience the impacts of low transit supply as well. In addition, the findings suggest that residents of rural and small urban areas travel longer distances on their day-to-day activities. This paper attempts to advance the national research pertaining to transport disadvantage and provide a framework that can support planning and policy decisions at the community as well as at the state level. Highlights: A spatial approach is proposed to assess transport disadvantage. The proposed approach accounts for accessibility, mobility, and realized travel behavior. From a policy perspective, assessment should not be limited to realized behavior. Rural and small urban Indiana has a low density of opportunities. Low transit supply impacts are unequally distributed to Indiana's population groups.